Mental and Hedonistic Determinants Shaping Physical Activity Engagement among Generation Z - WAŚKOWSKI, Zygmunt; DELIŃSKA, Liwia; WANAT, Tomasz (Journal of Environmental Management and Tourism; Vol 16 No 3 (2025): JEMT, Volume XVI, Issue 3(79), Fall 2025, 2025)
Consumers may exhibit various attitudes toward specific products, services, or activities. Regarding physical activity, a distinction can be made between a passive attitude, characterized by a lack of interest in sports and recreation, and an active attitude, manifested by participation in various forms of physical activity. This attitude is reflected in certain consumer behaviors in the sports market. The research question in this article is whether an interest in sports and recreation among Generation Z representatives translates into their actual physical activity. Additionally, moderating factors affecting this relationship, particularly the level of knowledge about sports and the availability of sports infrastructure and events, are analyzed. The purpose of the article is to identify and determine the impact of selected determinants that incline Generation Z representatives to engage in physical activity. The study was conducted using a survey method with the CAWI technique on a sample of 433 respondents representing Generation Z. Data were collected in the fourth quarter of 2024 in three metropolitan areas in Poland. The analysis of the results indicates that an interest in sports is a factor that encourages young people to engage in physical activity, which is strengthened by knowledge about sports. However, the availability of sports infrastructure and sporting events does not have a significant impact on the actual level of physical activity among Gen Z. In promoting sports participation among members of Generation Z, disseminating knowledge about physical activity is crucial. Shaping awareness and consumer attitudes proves to be more effective than merely increasing the availability of sports infrastructure or organizing sporting events.